Implementasi Sistem Keamanan Wi-Fi Menggunakan Sistem Operasi Kali Linux Di SMKN 5 Dumai - Satria, Devit (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Current technological advances force all existing computer networks to be able to show that the security system model continues to be considered very important for users who want a good security from outside the network because the internet is a computer network medium that has very open access in the world. . The purpose of this paper is to analyze the security of a wireless network using the wpa and wpa2-psk methods to determine whether the network is safe to use. Furthermore, testing where n the network uses Kali Linux as the operating system. Wireless network security analysis using 1 computer to perform testing. The first test uses aircrack and the second test uses aircrack injection. The test target is the security of the wireless network using the wpa and wpa2-psk security methods. The results obtained can determine the level of security of the wireless network so there will be no security breach on the wireless network. And security analysis using the wpa2-psk method is more difficult to get a handshake because it has superior security.